Mulching and fertigation in okra (Abelmoschus esculentus) - NARAYANANKUTTY, C; SREELATHA, U; PRAMEELA, K P (The Indian Journal of Agricultural Sciences, 2017)
Experiment was conducted in okra (Abelmoschus esculentus L.) (var. Arka Anamika) to study the effect of drip irrigation with and without mulch along with fertigation at Agricultural Research Station, Mannuthy during 2012-13 and 2013-14. Treatments comprised two levels of irrigation, viz. I1: drip irrigation at 0.60 ET, I2: drip irrigation at 0.80 ET, two mulching treatments, viz. M1: mulching with 30 μ silver black polythene sheet, M2: without mulching and three fertigation treatments, viz. F1: 75% RDF (Recommended Dose of Fertilizer), F2: 100 % RDF and F3: 125% RDF. Drip irrigation, fertigation and mulching treatments induced earliness and significantly enhanced the number of fruits and yield/plant. Treatment I2F3M1 recorded significantly highest yield of 1.46 kg/plant and number of fruits (53.88). Mulching had positive significant impact on yield and the results were significant even when irrigation is given at 0.60 ET. All the treatments with mulch irrespective of irrigation and fertiliser levels recorded higher water use efficiency when compared to corresponding treatments without mulch. At the highest dose of fertilizer(125 % of RDF), the significant influence of mulch was evident at 0.60 as well as 0.80 ET. From the study conducted it can be recommended that if water is a limiting factor, irrigation at 0.60 ET along with mulching and 75% of recommended dose of fertilizer is sufficient to achieve a yield of 23.87 tonnes/ha. If there is sufficient water availability, a higher level of irrigation at 0.80 ET along with mulching and 125% of recommended dose of fertiliser can be adopted for achieving a significantly higher yield of 32.44 tonnes/ha.